Annual Plant Reviews Online 2018
DOI: 10.1002/9781119312994.apr0070
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Enzymic Cell Wall (glyco)Proteins

Abstract: The sections in this article areIntroductionHydroxyproline‐Rich Glycoproteins (HRGPs)Glycine‐Rich Proteins (GRPs)Other Wall ProteinsConclusionAcknowledgements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 225 publications
0
15
0
Order By: Relevance
“…Chimeric HRGPs have a recognized PFAM domain (black vertical lined box; B, E, and H) in addition to a HRGP region. (Johnson et al, 2003b), containing a PFAM domain like those identified in Populus trichocarpa using the revised BIO OHIO 2.0 program . Thus, Showalter et al (2010Showalter et al ( , 2016) used a combination of both bias and motifs to search for PRPs [45% or greater PVKCYT or 2 or more KKPCPP motifs or 2 or more PPVX(K/T) motifs] in Arabidopsis and P. trichocarpa.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Chimeric HRGPs have a recognized PFAM domain (black vertical lined box; B, E, and H) in addition to a HRGP region. (Johnson et al, 2003b), containing a PFAM domain like those identified in Populus trichocarpa using the revised BIO OHIO 2.0 program . Thus, Showalter et al (2010Showalter et al ( , 2016) used a combination of both bias and motifs to search for PRPs [45% or greater PVKCYT or 2 or more KKPCPP motifs or 2 or more PPVX(K/T) motifs] in Arabidopsis and P. trichocarpa.…”
mentioning
confidence: 99%
“…The protein backbone of AGPs is rich in the amino acids Pro/Hyp, Ala, Ser, and Thr of PAST (Schultz et al, 2002;Ma and Zhao, 2010;Showalter et al, 2010). A biased amino acid approach (50% or greater PAST) was developed to detect Arabidopsis (Arabidopsis thaliana) AGPs (Schultz et al, 2002), which also identified some EXTs and PRPs (Johnson et al, 2003b). Showalter et al (2010) modified this approach, developing BIO OHIO to include a mix of different strategies: a biased amino acid approach was used for AGPs (50% or greater PAST), a motif-based search for EXTs (two or more SP 4 [or SP 3 ]) motifs, and a combination of both methods for PRPs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, protein and transcript levels of shikimate/quinate HCT were lower in MS than in FS, consistent with lower lignin accumulation in MS. Moreover, four lipid-transfer proteins, eight serine proteases, and six fasciclin domain proteins (including 3 fasciclin-like arabinogalactan protein, FLA) were also enriched in stems, and these proteins have been reported to participate in cell wall maturation and secondary growth [31,32].…”
Section: Involvement Of Lignin Biosynthesis In the Regulation Of Stemmentioning
confidence: 99%